Penerapan Algoritma Apriori Pada Aplikasi Pemesanan Homestay di Desa Marinsow - Ayu Triana Situmorang; Vivi P Rantung; Gladly C Rorimpandey (Prosiding SISFOTEK, 2024)
Marinsow Village is one of the emerging tourist destinations in North Sulawesi, with its main attractions being the natural beauty and authentic local culture. Homestays have become a popular accommodation choice for tourists. This study aims to analyze the booking patterns of homestays in Marinsow Village by applying the Apriori algorithm, which is expected to help improve marketing strategies and optimize homestay booking services. The research method used is the prototype method, along with UML (Unified Modeling Language) to assist in system design. The data used in this study includes homestay bookings from August 2023 to May 2024, with a total of 750 transaction records. The analysis results reveal certain booking patterns that have the potential to be utilized in the development of more targeted promotional strategies and the enhancement of homestay services tailored to tourist preferences.